Vegetation Characteristics of the Orangutan (Pongo pygmaeus morio) Habitat in the Riparian Forest of Menamang, East Kalimantan - Tri , Tri Sayektiningsih; Amir , Amir Ma’ruf (Jurnal Wasian, 2017)
This study aimed to obtain information on vegetation characteristics of the orangutan’s habitat, including diversity, composition and structure, in the riparian forest of Menamang. Data was collected using a line-plot sampling method. The diversity index of trees and saplings was higher than seedlings. It was found that Lagestroemia speciosa showed the highest value of IVI at tree stage, accounted for 24.71 %. Fordia splendidissima then was dominant species at sapling stage with IVI of 29.94 %. Furthermore, Pterospermum diversifolium grew in abundance at seedling stage with IVI of 26.87 %. Overall, vegetation in the research location was consisted by relatively young trees characterized by the abundance of trees with diameter of ≥ 10 - 20 cm and height of < 15 m.